The Impact of COVID-19 on Foreign Investors : Evidence from the Quarterly Global MNE Pulse Survey for the Third Quarter of 2020 - Saurav, Abhishek; Kusek, Peter; Kuo, Ryan; Viney, Brody (World Bank, Washington, DC, 2020)
As the COVID-19 crisis extends into the second half of 2020, the outlook for both the pandemic and the associated economic crisis remains highly uncertain. In this environment, multinational enterprises (MNEs) need to weather a prolonged economic downturn while also navigating government policy responses to the pandemic and updating investment plans for an uncertain future. Given the importance of foreign direct investment (FDI) to the crisis and recovery, especially for developing countries, the World Bank Group’s Global Investment Climate Unit is conducting quarterly pulse surveys of MNE affiliates throughout 2020 to gauge the pandemic’s effect on foreign investors. According to previous rounds of the survey, four in five MNE affiliates experienced reduced revenue and profits, and three in four experienced a decline in supply chain reliability in the first quarter of 2020 (Saurav, Kusek, and Kuo, April 2020). The adverse impacts became near-universal in the second quarter of 2020, with over 90 percent of MNEs experiencing adverse effects (Saurav, Kusek, Kuo, and Viney, September 2020). A third round of the quarterly pulse survey, reflecting the third quarter of 2020, was administered in October and November 2020. The survey results show that the pandemic’s adverse effects remained widespread for MNE affiliates in the third quarter, with only limited improvements expected in the fourth quarter. While these survey results may not be generalizable to all developing countries, they are directionally indicative of MNEs’ experiences in developing countries.